2019
DOI: 10.1186/s12931-019-1019-9
|View full text |Cite
|
Sign up to set email alerts
|

Body composition, muscle function, and physical performance in fibrotic interstitial lung disease: a prospective cohort study

Abstract: BackgroundPatients with fibrotic interstitial lung disease (ILD) are frequently physically inactive and many ILD subtypes are characterized by risk factors for myopathy; however, the importance of body composition, muscle strength, and physical performance in this population is largely unknown.MethodsPatients were prospectively recruited from a specialized ILD clinic, baseline characteristics were collected from the clinical record, pulmonary function tests were performed per established protocols, and dyspnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 47 publications
4
40
1
Order By: Relevance
“…Individuals with a more impaired pulmonary function were found to have lower muscle mass and higher fat mass. Furthermore, men but not women in the study were found to have lower handgrip strength than expected compared to an age-matched healthy Canadian population [49].…”
Section: Discussioncontrasting
confidence: 60%
“…Individuals with a more impaired pulmonary function were found to have lower muscle mass and higher fat mass. Furthermore, men but not women in the study were found to have lower handgrip strength than expected compared to an age-matched healthy Canadian population [49].…”
Section: Discussioncontrasting
confidence: 60%
“…Pneumococcal vaccination and annual influenza vaccination are also appropriate in almost all patients with fibrotic ILD. With frequent loss of physical function and muscle mass in patients with severe and progressive ILD [38], pulmonary rehabilitation potentially relieves symptoms and improves exercise capacity [39]. Similarly, selected patients can benefit from long-term oxygen therapy [40].…”
Section: Non-pharmacologic Treatmentmentioning
confidence: 99%
“…Especially, we found significant genetic correlations between IPF and many body fat related traits. Different studies have found that obesity is a common comorbidity of IPF [38,39]. Lower body mass index (BMI) and body weight loss seemed to be related to poor outcomes [40].…”
Section: Discussionmentioning
confidence: 99%